Chekirbane, Anis - (:unkn) unknown (My University, 2026)
Dr. Anis Chekirbane is presently working as an Assistant Professor at the National Institute of Agronomy, University of Carthage, Tunisia. Founded in 1898, this institute is holding the top rank in Agricultural Engineering, specifically in the field of water resources. However, Dr. Chekirbane received his PhD in the field of Sustainable Environmental Studies from the University of Tsukuba, Japan. He completed his MS in Natural Resources Management from University of Carthage, Tunisia with very good result (rank 1st). Afterwards he got Japanese Government Scholarship for PhD degree leads by MEXT in Japan. In the meantime, Dr. Chekirbane worked as researcher in the Water Research and Technologies center in Tunisia from 2004 until 2020. He served as Principal Investigator (PI), International Consultant and member of several research projects. In addition, he is an author/co-author for 17 scientific journal articles. He is also a reviewer of several peer reviewed and indexed journals. Meanwhile, he attended several national and international conferences and workshops with oral presentation. His research interest focuses on water resources issues, including the characterization of groundwater flow systems, managed aquifer recharge and interaction between surface water and groundwater using GIS, geophysical methods, isotopic tracers, modeling approaches and smart monitoring and metering tools.